Development of a Mental Health Strategy in an Acute Trust – A New Role for Psychiatrists - Samuel Dearman; Roger Cable (BJPsych Open)
Aims: The aim was to develop a strategy for mental health and learning disabilities in an acute and community trust in North Cumbria, in response to the CQC report “Assessment of mental health services in acute trusts programme” published in 2020. The strategy also needed to align with the trust vision, values and objectives while developing a clear but simple overview of what is required to improve mental health services within the trust for people with a wide range of mental health difficulties and learning disabilities. We also describe novel and innovative roles for psychiatrists as a new area of professional practice.